Graphene oxide activates B cells with upregulation of granzyme B expression: evidence at the single-cell level for its immune-modulatory properties and anticancer activity. Issue 2 (19th November 2021) - Orecchioni, Marco; Fusco, Laura; Mall, Raghvendra; Bordoni, Valentina; Fuoco, Claudia; Rinchai, Darawan; Guo, Shi; Sainz, Raquel; Zoccheddu, Martina; Gurcan, Cansu; Yilmazer, Acelya; Zavan, Barbara; et al.
Abstract : While both graphene oxide and amino functionalized graphene oxide exert strong pro-activating properties on B cells, the latter is also able to induce a B cell receptor signaling dysregulation, which triggers the production of granzyme B. Abstract : We recently found by single-cell mass cytometry that ex vivo human B cells internalize graphene oxide (GO). The functional impact of such uptake on B cells remains unexplored. Here, we disclosed the effects of GO and amino-functionalized GO (GONH2 ) interacting with human B cells in vitro and ex vivo at the protein and gene expression levels. Moreover, our study considered three different subpopulations of B cells and their functionality in terms of: (i) cytokine production, (ii) activation markers, (iii) killing activity towards cancer cells. Single-cell mass cytometry screening revealed the higher impact of GO on cell viability towards naïve, memory, and plasma B cell subsets. Different cytokines such as granzyme B (GrB) and activation markers, like CD69, CD80, CD138, and CD38, were differently regulated by GONH2 compared to GO, supporting possible diverse B cell activation paths. Moreover, co-culture experiments also suggest the functional ability of both GOs to activate B cells and therefore enhance the toxicity towards HeLa cancer cell line. Complete transcriptomic analysis on a B cell line highlighted the distinctive GO and GONH2 elicited responses, inducing pathways such as B cell receptor and CD40 signaling pathways, key players for GrB secretion. B cells were regularly left behind the scenes in graphene biological studies; our results may open new horizons in the development of GO-based immune-modulatory strategies having B cell as main actors.